Home from home: an auto/biographical narrative research pilgrimage - West, Linden (Adult Education Discourses, 2024)
The paper embodies a kind of research pilgrimage: informed by actual pilgrimage and the power of metaphor and expressive writing. The starting point is hesitant first steps under the gaze of scientific literalism as well as youthful conceit. It encompasses historical research on Richard Henry Tawney – a key figure in workers’ education. It was followed by conventional psychological research in the 1980s into working-class student experience, but this was challenged by those at its heart: listen to us for a change, they said. Eventually, there were steps towards what I now call auto/biographical narrative research, and the influence of European colleagues and feminism was important in finding a good enough research home, and eventually more authenticity and depth. The journey in fact became an explicit, joyful play of metaphor, intimacy, cultural politics, and narrative dialectics. It included a subjective journey home, encompassing different ways of seeing, literature, subjective and unconscious life, a vulnerable yet resilient humanity, self, other and otherness. And, in the context of the contemporary rise of racism and fundamentalism, a reconnection with parents and the gifts and goodness of a lost, agentic working-class culture. The paper is a kind of meditation on research and how it can help in the fundamental work of memory, to build a better, more socially just, inclusive, and reflexively conscious world.